An Analysis of Slang Words Used in Social Media (Instagram) - Sri Indra; Marhamah (RETORIKA: Jurnal Ilmu Bahasa, 2024)
The research titled "An Analysis of Slang Words Used in Social Media (Instagram)" investigates the use of slang in Instagram captions and comments. The study aims to describe the types and functions of slang words used by Instagram users and to understand the sociolinguistic factors influencing their usage. Through qualitative descriptive analysis, data were collected from various Instagram accounts, focusing on the frequency and context of slang word usage. The findings indicate that slang is prevalent on Instagram, serving to create a sense of community and belonging among users, while also reflecting cultural and social dynamics. This study provides valuable insights into the evolving nature of language in digital communication and highlights the importance of understanding slang as a linguistic phenomenon in social media interactions.